Sporogenesis and ultrastructure of spores in the fern Anemia hirsuta (Anemiaceae) - Rincón-Barón, Edgar Javier (2025)
Introduction: Research into the ontogeny of sporangia and sporogenesis of leptosporangiate ferns is scarce in the scientific literature. Objectives: To describe and analyze the ontogeny of sporangia, sporogenesis, micromorphology, and ultrastructure of mature spores of the fern Anemia hirsuta. Methods: Fertile fronds of A. hirsuta were processed according to standard protocols for sectioning and embedding samples in paraffin and resin. Sections in paraffin were stained with safranin-alcian blue, Toluidine Blue, and PAS/amidoblack. Sections in resin were stained with Toluidine Blue. The samples were prepared for observation under scanning electron microscopy (SEM) to yield detailed descriptions. Mature spores were analyzed by X-ray energy dispersion (XEDS). Ultrathin sections were obtained for transmission electron microscopy (TEM) observation. Results: The entire leptosporangium is formed from a basal and an apical cell derived from a single epidermal cell of the fertile pinna. The mature leptosporangia are globose, with a subapical ring and a short pedicel. During development, the tapetum is initially cellular, and then becomes plasmodial. The sporocytes undergo simultaneous meiotic division to form tetrads of spores in a tetrahedral arrangement. The exospore is formed first, with two layers, a very thin internal layer and a thick outer layer, followed by the endospore, and finally the perispore. The spores are trilete and muriform, with simple or branched siliceous microspines. The perispore associated with the muri and grooves appears to be highly organized with evident ultrastructural differences. Conclusions: The ontogeny of the sporangia and sporogenesis of A. hirsuta is similar to that previously described for leptosporangiate ferns and recorded in some related fossil species. The highly structured and organized perispore is observed. A high silica content in the microspines of the sporodermis is herein reported for the first time in this group.